2022
DOI: 10.21203/rs.3.rs-2088682/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GADD34 activates p53 and may have utility as a marker of atherosclerosis

Abstract: We previously identified growth arrest and DNA-damage-inducible gene 34 (GADD34) as a marker of ischemic stroke. In the present study, serum levels of anti-GADD34 antibodies were found to be significantly higher in patients with acute ischemic stroke or chronic kidney disease compared to healthy donors. We then examined the biological function of GADD34 by transfection into human osteosarcoma U2OS cells. Knockdown of GADD34 by siRNA resulted in enhanced cell proliferation, which was suppressed by knockdown of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In terms of biomarker species, studies have reported enzyme, antigen, and, in recent years, nucleotide markers (1-3). However, there are still some reports on antibody markers, which include heat-shock 60-kD protein 1 (4), replication protein A2 (5), programmed cell death 11 (6), metalloproteinase 1, chromobox homolog 1, chromobox homolog 5 (7), DnaJ heat shock protein family (Hsp40) member C2 (8), adaptor-related protein complex 3 subunit delta 1 (9), serpin peptidase inhibitor, clade E member 1 (10), death-inducer obliterator 1, cleavage and polyadenylation specificity factor 2, forkhead box J2 (11) and thiosulfate sulfurtransferase-like domain-containing 2 (12) for acute ischemic stroke (AIS); ATPase, Ca ++ transporting, plasma membrane 4 (10), bone morphogenetic protein 1 (3,13), deoxyhypusine synthase (14), SH3 domain-binding protein 5 (15), prolyl carboxypeptidase (16), low-density lipoprotein receptor-related protein-associated protein 1 (17) and additional sex combs-like 2 (18) for atherosclerosis; nardilysin (19) for acute cardiac syndrome; and insulin (20), glutamic acid decarboxylase (21), adiponectin (22) and growth arrest and DNA-damage-inducible gene 34 (23,24), and proprotein convertase subtilisin/kexin type 9 (25) for diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of biomarker species, studies have reported enzyme, antigen, and, in recent years, nucleotide markers (1-3). However, there are still some reports on antibody markers, which include heat-shock 60-kD protein 1 (4), replication protein A2 (5), programmed cell death 11 (6), metalloproteinase 1, chromobox homolog 1, chromobox homolog 5 (7), DnaJ heat shock protein family (Hsp40) member C2 (8), adaptor-related protein complex 3 subunit delta 1 (9), serpin peptidase inhibitor, clade E member 1 (10), death-inducer obliterator 1, cleavage and polyadenylation specificity factor 2, forkhead box J2 (11) and thiosulfate sulfurtransferase-like domain-containing 2 (12) for acute ischemic stroke (AIS); ATPase, Ca ++ transporting, plasma membrane 4 (10), bone morphogenetic protein 1 (3,13), deoxyhypusine synthase (14), SH3 domain-binding protein 5 (15), prolyl carboxypeptidase (16), low-density lipoprotein receptor-related protein-associated protein 1 (17) and additional sex combs-like 2 (18) for atherosclerosis; nardilysin (19) for acute cardiac syndrome; and insulin (20), glutamic acid decarboxylase (21), adiponectin (22) and growth arrest and DNA-damage-inducible gene 34 (23,24), and proprotein convertase subtilisin/kexin type 9 (25) for diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%